Why do student teachers enrol for a teaching degree? A study of teacher recruitment in Portugal and Sweden - Flores, Maria Assunção (2014)
This paper reports on findings from an exploratory study carried out in Portugal and Sweden, concerning student teacher recruitment to Initial Teacher Education programmes. It addresses issues such as motivations and expectations of the student teachers regarding the teaching profession. Drawing upon existing related literature a questionnaire was designed and sent to student teachers in Portugal and in Sweden. In total, 112 and 157 student teachers participated in the study, respectively. Data suggest a given profile of a student teacher making it possible to analyse some of key characteristics in both countries. The comparison between countries in combination with suggestions and recommendations from student teachers indicate that the recruitment process may be supported if the information about the design, content and the aims of Initial Teacher Education programmes are clarified and made explicit.